(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
This essay attempts to question the basics principles od local development, which are framed, above all, between family entrepreneurships that generates the circulation on goods, as well as family and inter- neighborhood relations. The creation of this proposal originates from ancestral knowledge on family economies, mainly on rural communities, where a strong attachment to cultural patterns of reciprocal behaviors is still perceived. The purposes of this essay us to establish that the culture of entrepreneurship is an intrinsic activity to the Nicaraguan culture that dates to the first settlers. It should also be considered as a local strategy for development that resists the ruptures of the capitalist system, and its influence in the global economy, that affects directly and indirectly the local economies. This project is based on texts of references and argumentative comparisons, exposing that entrepreneurship is not a new invention. It is currently understood as a commercial element, obviating the value of the community use as an essential element of the local culture.